2013
DOI: 10.1002/term.1818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parathyroid hormone 1-34 on osteogenic and chondrogenic differentiation of human fracture haematoma-derived cellsin vitro

Abstract: Parathyroid hormone (PTH) 1-34 has been shown to accelerate fracture healing. Previously, we reported that progenitor cells with osteogenic and chondrogenic potential exist in human fracture haematoma, suggesting that the fracture haematoma-derived progenitor cells (HCs) contribute to fracture healing. However, there has been no study investigating the effect of PTH on HCs. We investigated the effect of pulsatile and continuous PTH treatment on human fracture HCs in vitro. HCs were isolated from seven patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several studies have identified potential mechanisms by which PTH (1–34) may enhance fracture healing [ 6 , 15 , 38 ]. PTH (1–34) may enhance fracture healing by two mechanisms: firstly by stimulating the differentiation of osteoblasts and secondly by promoting chondrocyte proliferation and differentiation and accelerating endochondral bone formation [ 9 , 11 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified potential mechanisms by which PTH (1–34) may enhance fracture healing [ 6 , 15 , 38 ]. PTH (1–34) may enhance fracture healing by two mechanisms: firstly by stimulating the differentiation of osteoblasts and secondly by promoting chondrocyte proliferation and differentiation and accelerating endochondral bone formation [ 9 , 11 , 39 ].…”
Section: Discussionmentioning
confidence: 99%